Sulfation of afimoxifene, endoxifen, raloxifene, and fulvestrant by the human cytosolic sulfotransferases (SULTs): A systematic analysis - Ying Hui; Lijun Luo; Lingtian Zhang; Katsuhisa Kurogi; Chunyang Zhou; Yoichi Sakakibara; Masahito Suiko; Ming-Cheh Liu (Elsevier, 2015)
Previous studies demonstrated that sulfate conjugation is involved in the metabolism of three commonly used breast cancer drugs, tamoxifen, raloxifene and fulvestrant. The current study was designed to systematically identify the human cytosolic sulfotransferases (SULTs) that are capable of sulfating raloxifene, fulvestrant, and two active metabolites of tamoxifen, afimoxifene and endoxifen. A systematic analysis using 13 known human SULTs revealed SULT1A1 and SULT1C4 as the major SULTs responsible for the sulfation of afimoxifene, endoxifen, raloxifene and fulvestrant. Kinetic parameters of these two human SULTs in catalyzing the sulfation of these drug compounds were determined. Sulfation of afimoxifene, endoxifen, raloxifene and fulvestrant under metabolic conditions was examined using HepG2 human hepatoma cells and MCF-7 breast cancer cells. Moreover, human intestine, kidney, liver, and lung cytosols were examined to verify the presence of afimoxifene/endoxifen/raloxifene/fulvestrant-sulfating activity.